Numerical Analysis on Boundary Layer Flow of a Dusty Fluid over a Permeable Shrinking Surface - Zaihan, Normiza Nazihah; Noorzehan Fazahiyah Md Shab, (Enhanced Knowledge in Sciences and Technology, 2023)
The numerical analysis on boundary layer flow of a dusty fluid over a permeable shrinking surface was studied. The purpose of this research is to study the effects of the governing parameters on the profiles of fluid and dust velocity profiles when there is fluid suction at the surface. Then, using the similarity transformation, the problem's governing equations are transformed into a system of ordinary differential equations. Then the Runge-Kutta-Fehlberg method in the Maple software are used to numerically solve the problem by using shooting technique. The obtained results were observed, compared, and represented in tables and graphs. The current findings are found to be in strong agreement with the results that were previously published. The fluid phase and dust phase velocities increased and the particle velocities decreased at the surface due to the drag coefficient . The dimensionless fluid-phase velocity profiles and the dimensionless dust-phase velocity profiles both increase as a result of the increase in the suction velocity through the shrinking sheet.